The Application of Accounting and Preferences for Sharia Finance Products at KSPPS Baitut Tamwil Tazakka, Pekalongan Regency - Arief Firmansyah; Mubayyinul Khoiri; R Nia Marotina; Lika Masroatul Khasanah; Rudiyanto Rudiyanto (SIL'AH: Jurnal Ekonomi Syariah, 2026)
This qualitative case study aims to describe Sharia accounting practices based on the Indonesian Sharia Financial Accounting Standards (PSAK) at the Tazakka Cooperative, whilst also exploring members’ preferences regarding the financial products on offer. Primary data was obtained through in-depth interviews with the cooperative’s board and management. The research findings indicate that the Tazakka Cooperative has implemented key standards such as PSAK 101 (presentation of financial statements), PSAK 102 (murabahah), and PSAK 105 (mudharabah), reflecting a commitment to transparency and Sharia compliance. Meanwhile, members showed a strong preference for the Eid al-Fitr Savings Scheme and Murabahah Financing due to their convenience and suitability for practical financial needs. This research contributes to highlighting the importance of integrating Sharia compliance with service innovation in enhancing member trust and the sustainability of Sharia cooperative activities.